Ranitidine in the prevention of gastric and duodenal ulcer relapse. Issue 5 (May 1983) - Alstead, E M; Ryan, F P; Holdsworth, C D; Ashton, M G; Moore, M
Abstract : Prophylactic maintenance therapy for one year using ranitidine 150 mg at night or a placebo was assessed in 68 patients whose gastric or duodenal ulcers had previously healed after therapy with ranitidine 150 mg twice daily or placebo. Gastroscopy was carried out on symptomatic relapse and at the end of the year. Of the duodenal ulcer group, seven out of 20 relapsed on ranitidine compared with 15 out of 17 on placebo (p less than 0.001). Of the gastric ulcer group one of 15 patients relapsed on ranitidine compared with 11 of 16 patients on placebo (p less than 0.005). There were no adverse effects from ranitidine during the trial period. Ranitidine in low dose maintenance therapy is therefore reasonably effective in the prevention of relapse of duodenal ulcers and appears to be particularly effective in preventing relapse of gastric ulcers at least for one year. As gastric ulcers occur more frequently in the older patients in whom there are often medical contraindications to surgery, maintenance treatment may be appropriate for many such patients.